2014
DOI: 10.1515/biol-2015-0004
|View full text |Cite
|
Sign up to set email alerts
|

Effect of cadmium stress on barley tissue damage and essential metal transport into plant

Abstract: Conductometric assessment of electrolyte leakage from spring barley plant organs subjected to higher cadmium concentrations 10-2 – 10-4 mol l-1 revealed serious tissue damage. Therefore plants were grown under controlled environment conditions in a phytotron in Knop´s nutrient solution in two variants – the control variant without cadmium and experimental variant treated during the growth of plants with CdCl2 solution of 10-5 mol l-1. Barley plants were then separated into roots, residual caryopses, leaf bases… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…Zn is beneficial for growth, while Cd is a dangerous heavy metal that can inhibit plant growth only at low concentration. In previous studies, researchers have found that Cd stress can reduce the absorption of Zn by plants [ 59 ], while the appropriate addition of Zn can reduce the absorption of Cd by plants and improve the utilization of other elements [ 60 ], but studies have also found that Zn The inhibition of Cd absorption depends on the ratio of the two concentrations [ 61 ]. The ZIP gene family may play a crucial role in regulating the transport of Zn and Cd.…”
Section: Discussionmentioning
confidence: 99%
“…Zn is beneficial for growth, while Cd is a dangerous heavy metal that can inhibit plant growth only at low concentration. In previous studies, researchers have found that Cd stress can reduce the absorption of Zn by plants [ 59 ], while the appropriate addition of Zn can reduce the absorption of Cd by plants and improve the utilization of other elements [ 60 ], but studies have also found that Zn The inhibition of Cd absorption depends on the ratio of the two concentrations [ 61 ]. The ZIP gene family may play a crucial role in regulating the transport of Zn and Cd.…”
Section: Discussionmentioning
confidence: 99%
“…Cd is an unessential element for plants. However, Cd can interact with other elements, such as zinc (Zn), copper (Cu), and manganese (Mn), and affect their uptake and translocation ( Lachman et al, 2015 ). Some studies have reported that Cd can affect plant development in various plant species by inhibiting the absorption of water and nutrients, resulting in various symptoms of injury in vivo or in vitro ( Li et al, 2008 ).…”
Section: Discussionmentioning
confidence: 99%
“…In addition to toxic metals, changes in the membranes of plant cells are mostly affected by water stress, changes in temperature and by frost. Toxicity of the metals (such as cadmium), can cause an accumulation in tissues, which consequently affects the metabolism of plants, particularly the photosynthetic apparatus (Lachman et al, 2015).…”
Section: Introductionmentioning
confidence: 99%